2019
DOI: 10.1186/s12889-019-6736-y
|View full text |Cite
|
Sign up to set email alerts
|

Iron status and risk factors of iron deficiency among pregnant women in Singapore: a cross-sectional study

Abstract: Background Iron deficiency is the most prevalent nutrient deficiency and the most common cause of anaemia worldwide. Because of the increased iron requirements during pregnancy, iron deficiency can lead to maternal anaemia and reduced newborn iron stores. We examined the proportion and risk factors of iron deficiency among pregnant women in a developed Asian country. Methods Within a prospective cohort in Singapore, 985 Asian women were assessed for iron status at 26–28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
4
26
2
6
Order By: Relevance
“…65 Data on folate intake and status in pregnant women were scarce and only available from Vietnam and Singapore (Table 3). 67,68 The mean daily intake of folate (440.8 μg) in Vietnam 68 was within the range recommended by FIGO (400-600 μg/day). Only Singapore 64 had data for median plasma folate level, which was reported as 34.4 nmol/L and above the WHO cut-off level for deficiency (<10 nmol/L).…”
Section: Micronutrient Status During Pregnancysupporting
confidence: 53%
See 1 more Smart Citation
“…65 Data on folate intake and status in pregnant women were scarce and only available from Vietnam and Singapore (Table 3). 67,68 The mean daily intake of folate (440.8 μg) in Vietnam 68 was within the range recommended by FIGO (400-600 μg/day). Only Singapore 64 had data for median plasma folate level, which was reported as 34.4 nmol/L and above the WHO cut-off level for deficiency (<10 nmol/L).…”
Section: Micronutrient Status During Pregnancysupporting
confidence: 53%
“…Data on iron, folate, and vitamin B12 intake and status in pregnant women were predominantly from sub-national cohort studies ( Table 3 ). 44 , 64 68 Data on iron intake were available only for Vietnam, Thailand, and Indonesia. 40 , 66 , 68 Indeed, in these regions, which had a high reported prevalence of anemia (37%–42%; Table 1 ), iron intake was suboptimal.…”
Section: Micronutrient Status During Pregnancymentioning
confidence: 99%
“…A study in Singapore reported that Malay and Indian pregnant women were more likely to have iron deficiency than ethnic Chinese. Differences in dietary practice, where ethnic Chinese eat more meat (source of haem-iron), Malay women consumed fewer fruits and vegetables and have a lower vitamin C intake, which can reduce iron absorption, while Indian women are tended to be vegetarian (24). All subjects were born from healthy Javanese mothers, so ethnicity did not affect the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Kurangnya suplementasi zat besi dikaitkan dengan hasil peningkatan defisiensi besi sedang dan berat, karena meningkatnya kebutuhan zat besi selama kehamilan maka setiap ibu hamil harus mendapat tambahan suplemen zat besi, dan ini dapat dijadikan sebagai strategi pencegahan terjadinya anemia. 20 Suplementasi zat besi sebanyak 30-60 mg diberikan kepada ibu yang memiliki cadangan zat besi di dalam tubuhnya dan 120-240 mg per hari untuk ibu yang tidak memiliki cadangan zat besi. 17 Karena jumlah besi yang diberikan pada janin dari ibu yang kekurangan besi tidak jauh berbeda dari jumlah yang di transfer secara normal, bayi yang baru lahir dengan ibu anemia berat tidak menderita anemia defisiensi besi.…”
Section: Pembahasanunclassified
“…4 Menurut Center for Deases Control and Prevention (CDC) mendefinisikan anemia sebagai kondisi dengan kadar hemoglobin kurang dari 11g/dl pada trimester pertama dan ketiga dan kurang dari 10,5 g/dl pada trimester kedua. 20 Ibu hamil dengan konsentrasi zat besi yang tinggi, tampaknya bahwa pemberian tablet besi harus dibatasi. 23 Selain pemeriksaan kadar hemoglobin, ibu hamil juga penting dilakukan pemeriksaan ferritin.…”
Section: Pembahasanunclassified